Vaterite coatings on electrospun polymeric fibers for biomedical applications; Journal of Biomedical Materials Research - Part A; Vol. 105, iss. 1 - Savelyeva M. S. Maria; Abalymov A. A. Anatoly; Lyubun G. P. German; Vidyasheva I. V. Irina; Yashchenok A. M. Alexey; Douglas T. E. L. Timothy; Gorin D. A. Dmitry Aleksandrovich; Parakhonskiy B. V. Bogdan (2017, 2017)
Title screen